Coping with dilemma: How German sport media users respond to sport mega events in autocratic countries. (December 2017) - Flemming, Felix; Lünich, Marco; Marcinkowski, Frank; Starke, Christopher
In recent years, sport mega events have been frequently awarded to autocratic countries whose regimes violate democratic values and human rights. Based on the theory of cognitive dissonance, we assume that this is a potential source of internal conflict for viewers, especially for sports enthusiasts and politically aware recipients. Special attention rests on the consequences of the recipients' strategies of addressing this predicament for important stakeholders of these events, namely the reporting media, the host country and sponsors. We conducted an online survey among 711 German respondents to examine how recipients cope with this dilemma using the forthcoming FIFA soccer World Cup 2018 in Russia as an example. Our results show that while recipients are strongly interested in soccer and politics, most of them do not necessarily perceive these two spheres as inextricably connected. Their awareness of sociopolitical issues in the context of sport events—and thus the decisive factor to explain cognitive dissonance—is arguably low. Still, when recipients experience cognitive dissonance they rely on certain strategies to reduce or avoid dissonance. They do not elude this dilemma by preferring sports broadcasting without coverage of the event's negative circumstances, but are actually willing to pass on parts of the tournament. They also do not denigrate the credibility of the media or emphasize positive aspects of the host country Russia. In fact, the recipients would prefer if the World Cup had not been awarded to Russia in the first place. However, respondents experiencing cognitive dissonance are also more likely to engage in political consumerism, by deliberately deciding against or in favor of products and sponsors depending on whether or not those are associated with the event.